Effect of Chewing Gum on Duration of Postoperative Ileus Following Laparotomy for Gastroduodenal Perforations: Protocol for a Randomized Controlled Trial - Muhumuza Joshua; Molen Selamo Fabrice; Mauricio William; La O Jorge Soria; Atumanyire Jethro; Godefroy Nyenke Bassara; Waziri Musa Abbas; Kithinji Stephen Mbae; Sonye Kiyaka Magugu; Leocadie Mugisho Munyerenkana; Sikakulya Franck Katembo; Kagenderezo ByaMungu Pahari; et al. (United Kingdom, 2025)
Background: Prolonged post-operative ileus is associated with increased risk of other complications, length of hospital stays and health care related costs. Chewing gum has been shown to reduce duration of ileus in many elective surgeries, but there is a paucity of randomised controlled trials (RCTs) on its effect on duration of ileus among patients undergoing emergency surgery, specifically patients with peritonitis. The aim of this study is to determine the effect of chewing gum on duration of postoperative ileus following laparotomy for gastroduodenal perforations.
Methods: This will be a randomised controlled trial done in 3 hospitals. Fifty-two patients will be randomised to 2 groups. Group A will receive chewing gum in addition to routine care, whereas group B will receive routine care only. The duration of post-operative ileus in the two groups which is the primary outcome, will be compared using the independent samples t-test in SPSS version 22. The length of hospital stay, in-hospital morbidity and mortality will be the secondary outcomes. This trial has been approved by Kampala International University research and Ethics committee (Ref No. KIU-2021-60) and Uganda national council of science and technology (Ref No. HS1665ES). Retrospective registration with the research registry has also been done (UIN: researchregistry8565).
Highlights: Prolonged post-operative ileus significantly contributes to adverse surgical outcomesChewing gum has been shown to reduce duration of ileus in many elective surgeriesThere is paucity of RCTs on role of chewing gum following surgery for peritonitis.